A bonded ferrite magnetic powder for injection molding and its preparation method and application
By ball milling the fine-grained and coarse-grained ferrite magnetic powder and matching it with specific rubber-type adhesives, the problem of taking into account both the flowability and magnetic properties of the injection molded magnets is solved, and the upper limit of use temperature and application areas are improved.
Patent Information
- Application Number
- CN202111271373.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-10-29
AI Technical Summary
The existing injection molded magnets are difficult to take into account both the fluidity and mechanical properties when improving magnetic properties, and cannot bend and deform, which limits their application fields.
The fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns and coarse-grained ferrite magnetic powder with a mean particle size of 3.0 to 6.0 microns are used to perform ball milling according to the weight ratio of fine-grained ferrite magnetic powder accounting for 10 to 35% by weight, combined with the specific formula Rubber-based binders, plasticizers and stabilizers are used to prepare bonded ferrite magnetic powder for injection molding with high compression density and high melt flow.
The fluidity of bonded ferrite magnetic powder for injection molding and the magnetic properties of injection molding flexible bonded magnets are significantly improved, and the upper limit of use temperature is increased from 80°C to 125°C, which broadens the application field and increases stability and reliability.
Smart Images

Figure BDA0003328104830000031 
Figure BDA0003328104830000041 
Figure BDA0003328104830000121
Abstract
Description
Technical Field
[0001] The invention relates to the field of injection-molded flexible bonded magnets, and in particular to bonded ferrite magnetic powder for injection molding and a preparation method and application thereof. Background Art
[0002] Injection molded magnets require magnetic powders with high fluidity to fill the mold and be injection molded into magnetic devices with complex shapes. Generally, the fluidity of magnetic powders is improved by reducing the volume ratio of magnetic powders in the magnets and increasing the volume ratio of binders in the magnets, but this will reduce the magnetic properties of injection molded magnets. Simply increasing the powder content will improve the magnetic properties to a certain extent, but it will reduce fluidity, deteriorate the mechanical properties of the magnets, and even cause problems such as failure to form.
[0003] In order to solve the above-mentioned problems in fluidity and magnetic properties, some existing patent documents disclose a coarse powder and fine powder mixing process, which mixes coarse ferrite magnetic powder and fine ferrite magnetic powder together as ferrite magnetic powder for injection molding, so that the fine ferrite magnetic powder can fill the pores of the coarse ferrite magnetic powder, thereby improving the filling rate of magnetic powder in the injection molded magnet, which to a certain extent achieves the purpose of improving the performance of the magnet. There are many patent documents disclosed in the prior art for this coarse powder and fine powder mixing process, and several cases are listed below for illustration:
[0004] (1) Chinese patent application CN200410034695.1 discloses a bonded magnet and ferrite powder for bonded magnets. The patent application uses a coarse powder with an average particle size of 2.5-5.0 microns, a fine powder with an average particle size of 0.5-1.0 microns, and the fine powder accounts for 15-40% of the weight of the mixed powder. The coarse powder and the fine powder are mixed by a wet method. The bonded magnet uses nylon 6 as a binder, and the magnet has a rigid shape.
[0005] (2) Chinese patent application CN200880108680.1 discloses a ferrite powder for bonded magnets, a method for manufacturing the same, and a bonded magnet using the same. The patent application uses a coarse powder with an average particle size of 1.0-5.0 microns, a fine powder with an average particle size of 0.2-1.0 microns, and the fine powder accounts for 15-40% of the weight of the mixed powder. The bonded magnet uses nylon 6 as the binder, and the magnet shape is rigid.
[0006] (3) Chinese patent application CN201080016639.9 discloses a ferrite powder for bonded magnets, a method for manufacturing the same, and a bonded magnet using the same. The patent application uses a mixture of coarse powder and fine powder, and does not clearly specify the average particle size range of the coarse powder and the fine powder. The fine powder accounts for 15-40% of the weight of the mixed powder. The bonded magnet uses nylon 6 as the binder, and the magnet is rigid in shape.
[0007] It can be seen from the above documents that the coarse powder and fine powder mixing process in the prior art has at least the following problems:
[0008] (1) The coarse powder and fine powder mixing processes in the prior art are all used to prepare bonded magnets with a rigid magnet shape, and the binders used in the bonded magnets are all nylon binders. Such bonded magnets cannot be bent or deformed to fit complex components, and their application areas are greatly limited.
[0009] (2) In the prior art, the coarse powder and fine powder mixing process is to first manufacture the coarse powder and the fine powder separately, and then mix the coarse powder and the fine powder by dry mixing or wet mixing. In this method, the fine powder and the coarse powder cannot be densely combined after mixing, resulting in an increase in the volume of the coarse and fine mixed magnetic powder. When a high powder content molding is subsequently performed, due to the resistance of the binder in the molten state, it is more difficult for the fine powder in the coarse and fine mixed magnetic powder to fill the gaps between the coarse powders in the binder, resulting in an increase in the volume ratio of the magnetic powder in the magnet, which is not conducive to improving the fluidity and magnetic properties.
[0010] (3) The magnetic powder formula used in the coarse powder and fine powder mixing process in the prior art is unreasonable, which makes the particle size uniformity of coarse-grained ferrite magnetic powder and fine-grained ferrite magnetic powder poor, produces a lot of oversized magnetic powder particles and undersized magnetic powder particles, and the magnetic powder particle size is relatively dispersed, which is not conducive to the filling of fine-grained magnetic powder, thereby reducing the magnetic properties of the magnet.
[0011] In view of this, the present invention is proposed. Summary of the invention
[0012] The purpose of the present invention is to provide a bonded ferrite magnetic powder for injection molding and a preparation method and application thereof, so as to solve the above-mentioned technical problems existing in the prior art. The present invention can be used to prepare injection-molded flexible bonded magnets, so that the fluidity of the bonded ferrite magnetic powder for injection molding and the magnetic properties of the injection-molded flexible bonded magnets can be greatly improved, both exceeding the level of similar products in the prior art, and the upper limit of the use temperature of the prepared injection-molded flexible bonded magnet can be increased from 80°C in the prior art to 125°C, which broadens the application field of the injection-molded flexible bonded magnet and increases the stability and reliability of the injection-molded flexible bonded magnet.
[0013] The objective of the present invention is achieved through the following technical solutions:
[0014] A bonded ferrite magnetic powder for injection molding, wherein fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns and coarse-grained ferrite magnetic powder with an average particle size of 3.0 to 6.0 microns are added into a ball mill for ball milling in a weight ratio of 10 to 35 wt % of the fine-grained ferrite magnetic powder, thereby obtaining a coarse and fine mixed magnetic powder.
[0015] Preferably, the ball milling comprises: adding a ball milling aid into a ball mill for ball milling; the ball milling aid is prepared by mixing triethanolamine, ethylene glycol and water in a mass ratio of 0.5:0.5:10.
[0016] Preferably, the fine-grained ferrite magnetic powder contains 0.2% to 0.4 wt% of bismuth oxide, and the coarse-grained ferrite magnetic powder also contains 0.2% to 0.4 wt% of bismuth oxide.
[0017] Preferably, 15 g of the bonded ferrite magnetic powder for injection molding is placed in a cylindrical mold with a diameter of 25 mm, and a molding pressure of 80 KN is applied to press the green compact into a cylindrical compact. The thickness of the green compact is measured, and the compression density is calculated, thereby obtaining a compression density of 3.55 g / cm 3 above.
[0018] Preferably, the bonded ferrite powder for injection molding has a melt flow rate of 100 g or more per 10 minutes when subjected to the fluidity test in the following steps 1 to 3;
[0019] Step 1, 92 parts by weight of the bonded ferrite powder for injection molding, 1.0 parts by weight of a stabilizer, 1.0 parts by weight of a plasticizer and 6.0 parts by weight of a rubber adhesive are mixed in a mixer; wherein the rubber adhesive is a mixture of polyvinyl chloride, a thermoplastic polyurethane elastomer and a thermoplastic polyester elastomer in a weight ratio of 25:60:15;
[0020] Step 2, kneading the mixture obtained in step 1 at 170-180° C. to form kneaded particles with an average particle size of 3-4 mm;
[0021] Step 3: Place the mixed pellets obtained in step 2 on a melt flow index tester, measure the extrusion weight within 10 minutes at 190° C. and a load of 10 kg, and use it as the melt flow rate.
[0022] Preferably, when the bonded ferrite powder for injection molding is subjected to the intrinsic coercive force test and the residual magnetic flux density test in the following steps 1, 2, and 4, the injection molded flexible bonded magnet made of the bonded ferrite powder for injection molding has an intrinsic coercive force of 190 kA / m or more and a residual magnetic flux density of 296 mT or more;
[0023] Step 1, 92 parts by weight of the bonded ferrite powder for injection molding, 1.0 parts by weight of a stabilizer, 1.0 parts by weight of a plasticizer and 6.0 parts by weight of a rubber adhesive are mixed in a mixer; wherein the rubber adhesive is a mixture of polyvinyl chloride, a thermoplastic polyurethane elastomer and a thermoplastic polyester elastomer in a weight ratio of 25:60:15;
[0024] Step 2, kneading the mixture obtained in step 1 at 170-180° C. to form kneaded particles with an average particle size of 3-4 mm;
[0025] Step 4: Injection mold the mixed particles obtained in step 2 into a cylindrical injection-molded flexible bonded magnet with a diameter of 20 mm and a height of 10 mm in an orientation magnetic field of 8.0 kGS at a temperature of 190°C, wherein the direction of the orientation magnetic field is parallel to the central axis of the cylinder, and use a permanent magnetometer to measure its intrinsic coercive force and residual magnetic induction intensity.
[0026] A method for preparing bonded ferrite powder for injection molding comprises: adding fine-grained ferrite powder with an average particle size of 0.5 to 1.2 microns and coarse-grained ferrite powder with an average particle size of 3.0 to 6.0 microns into a ball mill for ball milling, with the fine-grained ferrite powder accounting for 10 to 35 wt %, thereby obtaining coarse and fine mixed magnetic powder, i.e., the bonded ferrite powder for injection molding.
[0027] Preferably, the ball milling comprises: adding a ball milling aid into a ball mill for ball milling; the ball milling aid is prepared by mixing triethanolamine, ethylene glycol and water in a mass ratio of 0.5:0.5:10.
[0028] An injection-molded flexible bonded magnet comprises the following raw materials in parts by weight:
[0029]
[0030]
[0031] The rubber adhesive is prepared by blending 20 to 25 parts by weight of polyvinyl chloride, 60 to 70 parts by weight of thermoplastic polyurethane elastomer and 10 to 15 parts by weight of thermoplastic polyester elastomer.
[0032] Preferably, the polyvinyl chloride is a SG9 model product that complies with the GB / T5761-2006 standard, and its average degree of polymerization is less than 650; the plasticizer is an environmentally friendly long-chain chlorinated paraffin plasticizer; and the stabilizer is an ultraviolet absorber UV531.
[0033] Compared with the prior art, the present invention combines coarse-grained ferrite powder and fine-grained ferrite powder of a specific average particle size with ball milling to prepare bonded ferrite powder for injection molding, and uses it in combination with specially formulated rubber adhesives, plasticizers, and stabilizers in specific proportions, thereby being able to prepare injection-molded flexible bonded magnets, and greatly improving the fluidity of the bonded ferrite powder for injection molding and the magnetic properties of the injection-molded flexible bonded magnets, both exceeding the levels of similar products at home and abroad, and being able to increase the upper limit of the use temperature of the prepared injection-molded flexible bonded magnets from 80°C of existing flexible bonded magnets to 125°C, which broadens the application field of the injection-molded flexible bonded magnets and increases their stability and reliability. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below; obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, which does not constitute a limitation of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0035] First, the terms that may be used in this article are explained as follows:
[0036] The term “and / or” means that either or both of them can be realized at the same time. For example, X and / or Y means both “X” or “Y” and “X and Y”.
[0037] The terms "include", "comprises", "contains", "has" or other descriptions with similar semantics should be interpreted as non-exclusive inclusion. For example, including certain technical feature elements (such as raw materials, components, ingredients, carriers, dosage forms, materials, dimensions, parts, components, mechanisms, devices, steps, procedures, methods, reaction conditions, processing conditions, parameters, algorithms, signals, data, products or products, etc.) should be interpreted as including not only certain technical feature elements explicitly listed, but also other technical feature elements known in the art that are not explicitly listed.
[0038] The term "consisting of..." means excluding any technical feature elements not explicitly listed. If this term is used in a claim, it will make the claim closed, so that it does not contain technical feature elements other than the technical feature elements explicitly listed, except for the conventional impurities related to them. If this term only appears in a clause of a claim, it only limits the elements explicitly listed in the clause, and the elements recorded in other clauses are not excluded from the overall claim.
[0039] The term "parts by weight" refers to the mass ratio of multiple components. For example, if component X is described as x parts by weight and component Y is y parts by weight, then the mass ratio of component X to component Y is x:y. 1 part by weight can represent any mass, for example, 1 part by weight can be represented as 1 kg or 3.1415926 kg. The sum of the parts by weight of all components is not necessarily 100 parts, but can be greater than 100 parts, less than 100 parts or equal to 100 parts. Unless otherwise specified, the parts, ratios and percentages described herein are all by mass.
[0040] When concentration, temperature, pressure, size or other parameters are expressed in the form of a numerical range, the numerical range should be understood to specifically disclose all ranges formed by the pairing of any upper limit, lower limit, and preferred value in the numerical range, regardless of whether the range is explicitly stated; for example, if a numerical range of "2 to 8" is stated, the numerical range should be interpreted as including ranges such as "2 to 7", "2 to 6", "5 to 7", "3 to 4 and 6 to 7", "3 to 5 and 7", "2 and 5 to 7", etc. Unless otherwise specified, the numerical ranges stated herein include both their end values and all integers and fractions within the numerical range.
[0041] The bonded ferrite magnetic powder for injection molding provided by the present invention and its preparation method and application are described in detail below. The contents not described in detail in the present invention belong to the prior art known to professionals and technicians in this field. If the specific conditions are not specified in the embodiments of the present invention, they are carried out according to the conventional conditions in the field or the conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used in the embodiments of the present invention, they are all conventional products that can be purchased commercially.
[0042] (I) A bonded ferrite powder for injection molding
[0043] The present invention provides a bonded ferrite magnetic powder for injection molding. The bonded ferrite magnetic powder for injection molding is prepared by adding fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns and coarse-grained ferrite magnetic powder with an average particle size of 3.0 to 6.0 microns into a ball mill for ball milling, with the fine-grained ferrite magnetic powder accounting for 10 to 35 wt %, thereby obtaining a coarse and fine mixed magnetic powder.
[0044] The weight ratio of the fine-grained ferrite magnetic powder of 10 to 35 wt % means that the fine-grained ferrite magnetic powder accounts for 10 to 35 wt % of the total of the fine-grained ferrite magnetic powder and the coarse-grained ferrite magnetic powder.
[0045] In the prior art, the particle size distribution of conventional bonded ferrite powder for injection molding is normally distributed, and the waveform of its laser particle size distribution shows a single peak value. Its compression density is generally 3.3g / cm 3The three patent application documents mentioned in the background technology of this application are ferrite magnetic powders using a coarse powder and fine powder mixing process. The waveform of its laser particle size distribution will have multiple peaks, and its compressed density can reach 3.5g / cm 3 The inventors have found that by ball milling fine ferrite powder with an average particle size of 0.5 to 1.2 microns and coarse ferrite powder with an average particle size of 3.0 to 6.0 microns as raw materials, a coarse and fine mixed magnetic powder with a very high compression density can be obtained. The compression density of the coarse and fine mixed magnetic powder is at least 3.55 g / cm 3 This can achieve a smaller volume percentage of the same mass percentage of magnetic powder in the binder, thereby relatively increasing the volume ratio of the binder, greatly improving the fluidity of the coarse and fine mixed magnetic powder and the magnetic properties of the injection-molded flexible bonded magnet prepared from the coarse and fine mixed magnetic powder, effectively achieving both high magnetic properties and high fluidity.
[0046] In a typical but non-limiting embodiment of the present invention, the fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns is a fine-grained ferrite magnetic powder with an average particle size of 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1 or 1.2 microns.
[0047] In a typical but non-limiting embodiment of the present invention, the coarse-grained ferrite magnetic powder with an average particle size of 3.0 to 6.0 microns is a coarse-grained ferrite magnetic powder with an average particle size of 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9 or 6.0 microns.
[0048] In a typical but non-limiting embodiment of the present invention, the weight ratio of the fine-grained ferrite powder of 10 to 35wt% is that the fine-grained ferrite powder accounts for 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt% or 35wt% of the total of the fine-grained ferrite powder and the coarse-grained ferrite powder.
[0049] In a preferred embodiment of the present invention, the ball milling comprises: adding fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns, coarse-grained ferrite magnetic powder with an average particle size of 3.0 to 6.0 microns and a ball milling aid into a ball mill for ball milling, thereby obtaining a coarse and fine mixed magnetic powder; the ball milling aid can be a ball milling aid in the prior art, but it is best to use a ball milling aid provided by the present invention, which is a mixture of triethanolamine, ethylene glycol and water in a mass ratio of 0.5:0.5:10; different from the prior art, the present invention combines coarse-grained ferrite magnetic powder and fine-grained ferrite magnetic powder with a specific average particle size and ball milling to prepare a coarse and fine mixed magnetic powder, and adds the ball milling aid provided by the present invention during the ball milling process. The ball milling aid is a mixture of triethanolamine, ethylene glycol and water in a mass ratio of 0.5:0.5:10, thereby making the coarse-grained ferrite magnetic powder and the fine-grained ferrite magnetic powder more evenly mixed and dispersed during the ball milling process, reducing the friction resistance between the magnetic powders, being beneficial to the adaptive optimization and improvement of the bonding surface morphology and the overall average particle size of the coarse-grained ferrite magnetic powder and the fine-grained ferrite magnetic powder, eliminating the pores between the two to the greatest extent, making the coarse-grained ferrite magnetic powder and the fine-grained ferrite magnetic powder more closely and organically combined, further reducing the volume of the coarse-fine mixed magnetic powder, and improving the compression density of the coarse-fine mixed magnetic powder. The minimum compression density also exceeds the level of the three existing patent application documents mentioned in the background technology of this application.
[0050] In a typical but non-limiting embodiment of the present invention, the ball milling time is 0.5 to 1.0 hour.
[0051] In a typical but non-limiting embodiment of the present invention, the ball milling is performed using a JM-2L wet ball mill in the prior art.
[0052] In a preferred embodiment of the present invention, the fine-grained ferrite magnetic powder contains 0.2% to 0.4wt% of bismuth oxide, and / or the coarse-grained ferrite magnetic powder also contains 0.2% to 0.4wt% of bismuth oxide; preferably, both the fine-grained ferrite magnetic powder and the coarse-grained ferrite magnetic powder contain 0.2% to 0.4wt% of bismuth oxide; that is, the fine-grained ferrite magnetic powder is added with 0.2% to 0.4wt% of bismuth oxide accounting for the total weight of the fine-grained ferrite magnetic powder, and the coarse-grained ferrite magnetic powder is also added with 0.2% to 0.4wt% of bismuth oxide accounting for the total weight of the coarse-grained ferrite magnetic powder. Except for bismuth oxide, the other components of the fine-grained ferrite magnetic powder can adopt the components of ferrite magnetic powder in the prior art, and the other components of the coarse-grained ferrite magnetic powder can also adopt the components of ferrite magnetic powder in the prior art. The present invention adds a specific proportion of bismuth oxide to the composition formula of fine-grained ferrite magnetic powder and coarse-grained ferrite magnetic powder, so that the particle size of fine-grained ferrite magnetic powder and coarse-grained ferrite magnetic powder can be made finer and more uniform, and the generation of over-large magnetic powder particles and over-small magnetic powder particles is reduced, so that the magnetic powder particle size is more concentrated, and the average particle size control is more accurate, which is conducive to the fine-grained ferrite magnetic powder filling into the gaps of the coarse-grained ferrite magnetic powder, thereby improving the magnetic properties of the flexible bonded magnet prepared by these magnetic powders, and can also improve the fluidity of these magnetic powders at the same time.
[0053] In a typical but non-limiting embodiment of the invention, the fine-grained ferrite magnetic powder contains 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39% or 0.40wt% bismuth oxide.
[0054] In a typical but non-limiting embodiment of the invention, the coarse-grained ferrite magnetic powder contains 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39% or 0.40wt% bismuth oxide.
[0055] In a preferred embodiment of the present invention, the fine-grained ferrite magnetic powder can be prepared by the magnetic powder preparation method in the prior art; for example, the fine-grained ferrite magnetic powder can be prepared by the process of "raw material mixing->balling->drying->sintering->crushing->ball milling->tempering->PH value treatment->drying and crushing" in the prior art. In a preferred embodiment of the present invention, the coarse-grained ferrite magnetic powder can be prepared by the magnetic powder preparation method in the prior art; for example, the coarse-grained ferrite magnetic powder can be prepared by the process of "raw material mixing->balling->drying->sintering->crushing->ball milling->tempering->PH value treatment->drying and crushing" in the prior art. In a preferred embodiment of the present invention, 15 grams of the bonded ferrite magnetic powder for injection molding provided by the present invention is placed in a cylindrical mold with a diameter of 25 mm, and a molding pressure of 80KN is applied to press it into a cylindrical green compact, the thickness of the green compact is measured, and the compression density is calculated, so that the compression density (CD) of the bonded ferrite magnetic powder for injection molding is 3.55g / cm 3 above.
[0056] In a preferred embodiment of the present invention, the bonded ferrite powder for injection molding provided by the present invention has a melt flow rate of 100 g / 10 minutes or more when the fluidity test is performed in the following steps 1 to 3:
[0057] Step 1: Mix 92 parts by weight of the bonded ferrite powder for injection molding, 1.0 parts by weight of a stabilizer, 1.0 parts by weight of a plasticizer and 6.0 parts by weight of a rubber adhesive using a mixer; wherein the rubber adhesive is a mixture of polyvinyl chloride, a thermoplastic polyurethane elastomer and a thermoplastic polyester elastomer in a weight ratio of 25:60:15.
[0058] Step 2: knead the mixture obtained in step 1 at 170-180° C. to prepare kneaded particles with an average particle size of 3-4 mm.
[0059] Step 3: Place the mixed pellets obtained in step 2 on a melt flow index tester, and measure the extrusion weight within 10 minutes at 190° C. and a load of 10 kg, which is taken as the melt flow rate (unit: g / 10 minutes).
[0060] In a preferred embodiment of the present invention, when the bonded ferrite powder for injection molding provided by the present invention is subjected to the intrinsic coercive force test and the residual magnetic flux density test in the following steps 1, 2, and 4, the injection molded flexible bonded magnet made by using the bonded ferrite powder for injection molding has an intrinsic coercive force (iHc) of 190 kA / m or more and a residual magnetic flux density (Br) of 296 mT or more:
[0061] Step 1: Mix 92 parts by weight of the bonded ferrite powder for injection molding, 1.0 parts by weight of a stabilizer, 1.0 parts by weight of a plasticizer and 6.0 parts by weight of a rubber adhesive using a mixer; wherein the rubber adhesive is a mixture of polyvinyl chloride, a thermoplastic polyurethane elastomer and a thermoplastic polyester elastomer in a weight ratio of 25:60:15.
[0062] Step 2: knead the mixture obtained in step 1 at 170-180° C. to prepare kneaded particles with an average particle size of 3-4 mm.
[0063] Step 4: Injection mold the mixed particles obtained in step 2 into a cylindrical injection-molded flexible bonded magnet with a diameter of 20 mm and a height of 10 mm in an orientation magnetic field of 8.0 kGS at a temperature of 190°C, wherein the direction of the orientation magnetic field is parallel to the central axis of the cylinder, and use a permanent magnetometer to measure its intrinsic coercive force and residual magnetic induction intensity.
[0064] (II) A method for preparing bonded ferrite powder for injection molding
[0065] The present invention provides a method for preparing bonded ferrite powder for injection molding, which is used to prepare the bonded ferrite powder for injection molding provided by the present invention. The method specifically comprises the following steps: adding fine-grained ferrite powder with an average particle size of 0.5 to 1.2 microns and coarse-grained ferrite powder with an average particle size of 3.0 to 6.0 microns into a ball mill for ball milling, with the fine-grained ferrite powder accounting for 10 to 35 wt %, thereby obtaining a coarse and fine mixed magnetic powder, which is the bonded ferrite powder for injection molding provided by the present invention.
[0066] In a preferred embodiment of the present invention, the ball milling includes: adding fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns, coarse-grained ferrite magnetic powder with an average particle size of 3.0 to 6.0 microns and a ball milling aid into a ball mill for ball milling, thereby obtaining a coarse and fine mixed magnetic powder; the ball milling aid can adopt the ball milling aid in the prior art, but it is best to adopt the ball milling aid provided by the present invention, which is a mixture of triethanolamine, ethylene glycol and water in a mass ratio of 0.5:0.5:10.
[0067] In a preferred embodiment of the present invention, the fine-grained ferrite magnetic powder contains 0.2% to 0.4wt% of bismuth oxide, and / or the coarse-grained ferrite magnetic powder also contains 0.2% to 0.4wt% of bismuth oxide; preferably, both the fine-grained ferrite magnetic powder and the coarse-grained ferrite magnetic powder contain 0.2% to 0.4wt% of bismuth oxide; that is, the fine-grained ferrite magnetic powder is added with 0.2% to 0.4wt% of bismuth oxide accounting for the total weight of the fine-grained ferrite magnetic powder, and the coarse-grained ferrite magnetic powder is also added with 0.2% to 0.4wt% of bismuth oxide accounting for the total weight of the coarse-grained ferrite magnetic powder. Except for bismuth oxide, the other components of the fine-grained ferrite magnetic powder can adopt the components of ferrite magnetic powder in the prior art, and the other components of the coarse-grained ferrite magnetic powder can also adopt the components of ferrite magnetic powder in the prior art.
[0068] In a preferred embodiment of the present invention, the fine-grained ferrite magnetic powder can be prepared by the magnetic powder preparation method in the prior art; for example: the fine-grained ferrite magnetic powder can be prepared by the process of "raw material mixing->ball making->drying->sintering->crushing->ball milling->tempering->PH value treatment->drying and crushing" in the prior art.
[0069] In a preferred embodiment of the present invention, the coarse-grained ferrite magnetic powder can be prepared by the magnetic powder preparation method in the prior art; for example: the coarse-grained ferrite magnetic powder can be prepared by the process of "raw material mixing->ball making->drying->sintering->crushing->ball milling->tempering->PH value treatment->drying and crushing" in the prior art.
[0070] (III) An injection molded flexible bonded magnet
[0071] The present invention also provides an injection molded flexible bonded magnet, comprising the following raw materials in parts by weight: 92-93 parts of the bonded ferrite powder for injection molding provided by the present invention, 5-6 parts of a rubber binder, 1-1.5 parts of a plasticizer and 0.5-1 part of a stabilizer.
[0072] In a preferred embodiment of the present invention, the rubber adhesive is blended by 20-25 parts by weight of polyvinyl chloride (PVC), 60-70 parts by weight of thermoplastic polyurethane elastomer (TPU) and 10-15 parts by weight of thermoplastic polyester elastomer (TPEE). The present invention creatively develops this special formula of rubber adhesive, and uses this special formula of rubber adhesive in a specific ratio with the above-mentioned bonded ferrite magnetic powder for injection molding provided by the present invention to prepare injection molded flexible bonded magnets, and can improve the upper limit of the use temperature of the prepared injection molded flexible bonded magnet, so that the upper limit of the use temperature of the flexible bonded magnet is increased from 80°C in the prior art to 125°C, which broadens the application field of the injection molded flexible bonded magnet and increases the stability and reliability of the injection molded flexible bonded magnet.
[0073] In a preferred embodiment of the present invention, the polyvinyl chloride (PVC) is a SG9 product conforming to the GB / T5761-2006 standard, and its average degree of polymerization is less than 650; the use of such polyvinyl chloride can greatly improve the melt fluidity of the magnet.
[0074] In a preferred embodiment of the present invention, the thermoplastic polyurethane elastomer (TPU) adopts the thermoplastic polyurethane elastomer model H570 in the prior art; the use of this thermoplastic polyurethane elastomer (TPU) and thermoplastic polyester elastomer (TPEE) mixed as a binder can improve the heat resistance of the flexible adhesive magnet and enable the use temperature of the flexible adhesive magnet to reach 125°C.
[0075] In a preferred embodiment of the present invention, the thermoplastic polyester elastomer (TPEE) adopts the thermoplastic polyester elastomer model H2525 in the prior art; the use of this thermoplastic polyester elastomer (TPEE) and thermoplastic polyurethane elastomer (TPU) mixed as a binder can improve the heat resistance of the flexible adhesive magnet and enable the use temperature of the flexible adhesive magnet to reach 125°C.
[0076] In a preferred embodiment of the present invention, the plasticizer is an environmentally friendly long-chain chlorinated paraffin plasticizer; the plasticizer plays the role of plasticization and lubrication.
[0077] In a preferred embodiment of the present invention, the stabilizer is an ultraviolet absorber UV531; the stabilizer improves the aging resistance of the magnet.
[0078] Compared with the prior art, the bonded ferrite powder for injection molding, the preparation method of the bonded ferrite powder for injection molding, and the injection molded flexible bonded magnet provided by the present invention have at least the following advantages:
[0079] (1) Different from the prior art, the present invention combines coarse-grained ferrite magnetic powder and fine-grained ferrite magnetic powder of a specific average particle size with ball milling to prepare coarse and fine mixed magnetic powder, and adds the ball milling aid creatively developed by the present invention during the ball milling process, so that the coarse-grained ferrite magnetic powder and the fine-grained ferrite magnetic powder can be mixed and dispersed more evenly during the ball milling process, reducing the friction resistance between the magnetic powders, which is beneficial to the adaptive optimization and improvement of the bonding surface morphology and the overall average particle size of the coarse-grained ferrite magnetic powder and the fine-grained ferrite magnetic powder, eliminating the pores between the two to the greatest extent, making the coarse-grained ferrite magnetic powder and the fine-grained ferrite magnetic powder more closely and organically combined, further reducing the volume of the coarse-fine mixed magnetic powder, and improving the compression density of the coarse-fine mixed magnetic powder. The lowest compression density also exceeds the level of the three existing patent application documents mentioned in the background technology of this application.
[0080] (2) The present invention adds a specific proportion of bismuth oxide to the composition formula of fine-grained ferrite magnetic powder and coarse-grained ferrite magnetic powder, which can make the particle size of fine-grained ferrite magnetic powder and coarse-grained ferrite magnetic powder more refined and more uniform, reduce the generation of overly large magnetic powder particles and undersized magnetic powder particles, make the magnetic powder particle size more concentrated, and control the average particle size more accurately, which is beneficial to the filling of fine-grained ferrite magnetic powder, thereby improving the magnetic properties of flexible bonded magnets prepared from these magnetic powders, and can also improve the fluidity of these magnetic powders at the same time.
[0081] (3) The coarse powder and fine powder mixing processes in the prior art are all used to prepare rigid magnets, and none is used to prepare flexible magnets. In particular, the use of coarse and fine mixed magnetic powders with high compression density and high melt fluidity to prepare injection-molded flexible bonded magnets with excellent magnetic properties is a technical gap. The present invention combines coarse ferrite magnetic powders and fine ferrite magnetic powders with a specific average particle size with ball milling to prepare injection-molded bonded ferrite magnetic powders with high compression density and high melt fluidity, and uses them in combination with specially formulated rubber binders, plasticizers, and stabilizers in a specific proportion, so that injection-molded flexible bonded magnets with excellent magnetic properties can be prepared, and the fluidity of the bonded ferrite magnetic powders for injection molding and the magnetic properties of the injection-molded flexible bonded magnets can be greatly improved, both exceeding the level of similar products at home and abroad, and the upper limit of the use temperature of the prepared injection-molded flexible bonded magnets can be increased from 80°C of the existing flexible bonded magnets to 125°C, which broadens the application field of the injection-molded flexible bonded magnets and increases their stability and reliability.
[0082] In summary, it can be seen that the embodiments of the present invention can be used to prepare injection molded flexible bonded magnets, which can greatly improve the fluidity of bonded ferrite powder for injection molding and the magnetic properties of the injection molded flexible bonded magnets, both of which exceed the level of similar products in the prior art, and can increase the upper limit of the use temperature of the prepared injection molded flexible bonded magnets from 80°C in the prior art to 125°C, which broadens the application field of the injection molded flexible bonded magnets and increases the stability and reliability of the injection molded flexible bonded magnets.
[0083] In order to more clearly demonstrate the technical solution and technical effects provided by the present invention, the bonded ferrite powder for injection molding provided by the present invention and its preparation method and application are described in detail with specific embodiments below.
[0084] Example 1
[0085] An injection molded flexible bonded magnet, the preparation method of which may include the following steps:
[0086] Step A1, preparation of fine-grained ferrite magnetic powder: iron oxide and strontium carbonate are weighed according to a molar ratio of iron oxide: strontium carbonate = 5.78:1; bismuth oxide accounting for 0.2wt% of the total weight of the iron oxide and the strontium carbonate and strontium chloride accounting for 2.98wt% of the total weight of the iron oxide and the strontium carbonate are added to the iron oxide and the strontium carbonate, mixed together, granulated with water to form a ball with a diameter of 5 to 10 mm, and then dried in an oven at 130°C, the dried ball is placed in an electric furnace and sintered at 1250°C for 2 hours, then crushed with a jaw crusher, and then ball-milled for 6 hours with a JM-2L wet ball mill, thereby obtaining fine-grained ferrite magnetic powder with an average particle size of 0.5 microns.
[0087] Step A2, preparation of coarse-grained ferrite magnetic powder: weigh iron oxide and strontium carbonate according to the molar ratio of iron oxide: strontium carbonate = 5.78:1; add 0.2wt% of bismuth oxide and 2.98wt% of strontium chloride based on the total weight of the iron oxide and strontium carbonate to the iron oxide and strontium carbonate, mix them together, granulate them with water to form balls with a diameter of 5 to 10 mm, and then dry them in an oven at 130°C. The dried balls are placed in an electric furnace and sintered at 1250°C for 2 hours, and then crushed with a jaw crusher to obtain coarse-grained ferrite magnetic powder with an average particle size of 3.0 microns.
[0088] Step A3, preparation of coarse and fine mixed magnetic powder: the fine-grained ferrite magnetic powder with an average particle size of 0.5 microns described in step A1 and the coarse-grained ferrite magnetic powder with an average particle size of 3.0 microns described in step A2 are added into a ball mill in a weight ratio of 35wt% of the fine-grained ferrite magnetic powder and 65wt% of the coarse-grained ferrite magnetic powder, and then a ball milling aid (the ball milling aid is a mixture of triethanolamine, ethylene glycol, and water in a mass ratio of 0.5:0.5:10) is added into the ball mill for ball milling for 1.0 hour, and then the mixed powder is washed with water and dried, and then placed in an electric furnace for tempering at 950°C, and then pickled with a 2wt% hydrochloric acid solution to make its pH value reach 6-7, and then dried and crushed to obtain a coarse and fine mixed magnetic powder, which is the bonded ferrite magnetic powder for injection molding prepared in Example 1 of the present invention.
[0089] Step A4, preparation of injection molded flexible bonded magnet: 92 parts by weight of the coarse and fine mixed magnetic powder described in step A3, 6 parts by weight of rubber binder, 1 part by weight of plasticizer, and 1 part by weight of stabilizer are stirred together in a mixer, and then extruded and granulated by a twin-screw extruder. The obtained pellets are injection molded on an injection machine at an injection temperature of 175-190°C and a molded sample size of Φ20×10mm, thereby obtaining an injection molded flexible bonded magnet.
[0090] Wherein, the rubber adhesive is blended by 25 parts by weight of polyvinyl chloride (PVC), 65 parts by weight of thermoplastic polyurethane elastomer (TPU) and 10 parts by weight of thermoplastic polyester elastomer (TPEE). The use of thermoplastic polyurethane elastomer (TPU) and thermoplastic polyester elastomer (TPEE) mixed as an adhesive can improve the heat resistance of the flexible adhesive magnet and enable the use temperature of the flexible adhesive magnet to reach 125°C. The polyvinyl chloride (PVC) is a SG9 model product that meets the GB / T5761-2006 standard, and its average degree of polymerization is less than 650. The use of this polyvinyl chloride can greatly improve the melt fluidity of the magnet. The plasticizer is a long-chain chlorinated paraffin environmentally friendly plasticizer, which can play a role in plasticization and lubrication. The stabilizer is an ultraviolet absorber UV531, which can improve the aging resistance of the magnet.
[0091] Specifically, the temperature gradient and other parameters of the injection molding in step A4 are shown in Table 1 below:
[0092] Table 1
[0093] One section Second paragraph Three sections Magnetizing current Cooling and holding pressure 190℃ 185℃ 175℃ 70A Operation cycle 100S
[0094] Furthermore, the prior art product 1 (the prior art product 1 uses the injection magnetic powder BMZR-3D produced by Beikuang Magnetic Material Technology Co., Ltd. and the flexible magnet BMZR-Y3 made of the injection magnetic powder BMZR-3D) is compared with the bonded ferrite magnetic powder for injection molding prepared in step A3 of Example 1 of the present invention and the injection molded flexible bonded magnet prepared in step A4 for performance and temperature aging resistance. The results are shown in Table 2 and Table 3 below:
[0095] Table 2
[0096] characteristic unit Example 1 Existing technology products 1 Remanence(Br) mT 296 290 Coercivity (bHc) kA / m 176 170 Intrinsic coercivity (iHc) kA / m 210 205 Maximum magnetic energy product ((BH)max) <![CDATA[kJ / m 3 ]]> 16.8 15.9 Liquidity MFR g / 10min 105 85 Magnetic powder compression density <![CDATA[g / cm 3 ]]> 3.57 3.38
[0097] Table 3
[0098]
[0099]
[0100] It can be seen from Table 2 above that the compression density of traditional ferrite powder is generally 3.3g / cm 3 The compression density of the prior art product 1 in Table 2 reaches 3.38 g / cm 3 The compression density of the bonded ferrite powder for injection molding prepared in Example 1 of the present invention reaches 3.57 g / cm 3 At the same time, the fluidity and magnetic properties of the injection molded flexible bonded magnet prepared in Example 1 of the present invention are better than those of the prior art product 1. It can be seen from Table 3 above that the prior art product 1 is severely deformed and cracked under the heat aging conditions of 125°C×96h, while the injection molded flexible bonded magnet prepared in Example 1 of the present invention has almost no volume change under the heat aging conditions of 125°C×96h, which means that the upper limit of the use temperature of the injection molded flexible bonded magnet prepared in Example 1 of the present invention is increased from 80°C in the prior art to 125°C, which broadens the application field of the injection molded flexible bonded magnet and increases the stability and reliability of the injection molded flexible bonded magnet.
[0101] Example 2
[0102] An injection molded flexible bonded magnet, the preparation method of which may include the following steps:
[0103] Step B1, preparation of fine-grained ferrite magnetic powder: iron oxide and strontium carbonate are weighed according to the molar ratio of iron oxide: strontium carbonate = 5.78:1; bismuth oxide accounting for 0.2wt% of the total weight of the iron oxide and the strontium carbonate and strontium chloride accounting for 2.98wt% of the total weight of the iron oxide and the strontium carbonate are added to the iron oxide and the strontium carbonate, mixed together, granulated with water to form a ball with a diameter of 5 to 10 mm, and then dried in an oven at 130°C, the dried ball is placed in an electric furnace and sintered at 1250°C for 2 hours, then crushed with a jaw crusher, and then ball-milled for 4 hours with a JM-2L wet ball mill, thereby obtaining fine-grained ferrite magnetic powder with an average particle size of 0.8 microns.
[0104] Step B2, preparation of coarse-grained ferrite magnetic powder: weigh iron oxide and strontium carbonate according to the molar ratio of iron oxide: strontium carbonate = 5.78:1; add 0.2wt% of bismuth oxide and 2.98wt% of strontium chloride based on the total weight of the iron oxide and strontium carbonate to the iron oxide and strontium carbonate, mix them together, granulate them with water to form balls with a diameter of 5 to 10 mm, and then dry them in an oven at 130°C. The dried balls are placed in an electric furnace and sintered at 1250°C for 2 hours, and then crushed with a jaw crusher to obtain coarse-grained ferrite magnetic powder with an average particle size of 4.0 microns.
[0105] Step B3, preparation of coarse and fine mixed magnetic powder: the fine-grained ferrite powder with an average particle size of 0.8 microns described in step B1 and the coarse-grained ferrite powder with an average particle size of 4.0 microns described in step B2 are added into a ball mill in a weight ratio of 25wt% of the fine-grained ferrite powder and 75wt% of the coarse-grained ferrite powder, and then a ball milling aid (the ball milling aid is a mixture of triethanolamine, ethylene glycol and water in a mass ratio of 0.5:0.5:10) is added into the ball mill for ball milling for 1.0 hour, and then the mixed powder is washed with water and dried, and then placed in an electric furnace for tempering at 950°C, and then pickled with a 2wt% hydrochloric acid solution to make its pH value reach 6-7, and then dried and crushed to obtain a coarse and fine mixed magnetic powder, which is the bonded ferrite powder for injection molding prepared in Example 2 of the present invention.
[0106] Step B4, preparation of injection molded flexible bonded magnet: 92 parts by weight of the coarse and fine mixed magnetic powder described in step B3, 6 parts by weight of rubber binder, 1 part by weight of plasticizer and 1 part by weight of stabilizer are mixed together in a mixer, then extruded and granulated using a twin-screw extruder, and the obtained pellets are injection molded on an injection machine at an injection temperature of 175-190°C and a molded sample size of Φ20×10mm, thereby obtaining an injection molded flexible bonded magnet.
[0107] Wherein, the rubber adhesive is blended by 20 parts by weight of polyvinyl chloride (PVC), 70 parts by weight of thermoplastic polyurethane elastomer (TPU) and 10 parts by weight of thermoplastic polyester elastomer (TPEE). The use of thermoplastic polyurethane elastomer (TPU) and thermoplastic polyester elastomer (TPEE) mixed as an adhesive can improve the heat resistance of the flexible adhesive magnet and enable the use temperature of the flexible adhesive magnet to reach 125°C. The polyvinyl chloride (PVC) is a SG9 model product that meets the GB / T5761-2006 standard, and its average degree of polymerization is less than 650. The use of this polyvinyl chloride can greatly improve the melt fluidity of the magnet. The plasticizer is a long-chain chlorinated paraffin environmentally friendly plasticizer, which can play a role in plasticization and lubrication. The stabilizer is an ultraviolet absorber UV531, which can improve the aging resistance of the magnet.
[0108] Specifically, the temperature gradient and other parameters of the injection molding in step B4 are shown in Table 4 below:
[0109] Table 4
[0110] One section Second paragraph Three sections Magnetizing current Cooling and holding pressure 190℃ 185℃ 175℃ 70A Operation cycle 100S
[0111] Furthermore, the prior art product 2 (the prior art product 2 uses the injection magnetic powder BMZR-3C produced by Beikuang Magnetic Material Technology Co., Ltd. and the flexible magnet BMZR-Y2 made of the injection magnetic powder BMZR-3C) is compared with the bonded ferrite magnetic powder for injection molding prepared in step B3 of Example 2 of the present invention and the injection molded flexible bonded magnet prepared in step B4 for performance and temperature aging resistance. The results are shown in Table 5 and Table 6 below:
[0112] Table 5
[0113]
[0114]
[0115] Table 6
[0116]
[0117] It can be seen from Table 5 above that the compression density of traditional ferrite magnetic powder is generally 3.3g / cm 3 The compression density of the prior art product 2 in Table 5 reaches 3.39 g / cm 3 , while the compression density of the bonded ferrite powder for injection molding prepared in Example 2 of the present invention reaches 3.59 g / cm 3, and the fluidity and magnetic properties of the injection molded flexible bonded magnet prepared in Example 2 of the present invention are better than those of the prior art product 2. It can be seen from Table 6 above that the prior art product 2 is severely deformed and cracked under the heat aging conditions of 125°C×96h, while the injection molded flexible bonded magnet prepared in Example 2 of the present invention has almost no volume change under the heat aging conditions of 125°C×96h, which means that the upper limit of the use temperature of the injection molded flexible bonded magnet prepared in Example 2 of the present invention is increased from 80°C in the prior art to 125°C, which broadens the application field of the injection molded flexible bonded magnet and increases the stability and reliability of the injection molded flexible bonded magnet.
[0118] Example 3
[0119] An injection molded flexible bonded magnet, the preparation method of which may include the following steps:
[0120] Step C1, preparation of fine-grained ferrite magnetic powder: iron oxide and strontium carbonate are weighed according to a molar ratio of iron oxide: strontium carbonate = 5.78:1; bismuth oxide accounting for 0.2wt% of the total weight of the iron oxide and the strontium carbonate and strontium chloride accounting for 2.98wt% of the total weight of the iron oxide and the strontium carbonate are added to the iron oxide and the strontium carbonate, mixed together, granulated with water to form a ball with a diameter of 5 to 10 mm, and then dried in an oven at 130°C, the dried ball is placed in an electric furnace and sintered at 1250°C for 2 hours, then crushed with a jaw crusher, and then ball-milled for 2.5 hours with a JM-2L wet ball mill, thereby obtaining fine-grained ferrite magnetic powder with an average particle size of 1.2 microns.
[0121] Step C2, preparation of coarse-grained ferrite magnetic powder: weigh iron oxide and strontium carbonate according to the molar ratio of iron oxide: strontium carbonate = 5.78:1; add 0.2wt% of bismuth oxide and 2.98wt% of strontium chloride based on the total weight of the iron oxide and the strontium carbonate to the iron oxide and the strontium carbonate, mix them together, granulate them with water to form balls with a diameter of 5 to 10 mm, and then dry them in an oven at 130°C. The dried balls are placed in an electric furnace and sintered at 1250°C for 2 hours, and then crushed with a jaw crusher to obtain coarse-grained ferrite magnetic powder with an average particle size of 6.0 microns.
[0122] Step C3, preparation of coarse and fine mixed magnetic powder: the fine-grained ferrite magnetic powder with an average particle size of 1.2 microns described in step C1 and the coarse-grained ferrite magnetic powder with an average particle size of 6.0 microns described in step C2 are added into a ball mill in a weight ratio of 10wt% of the fine-grained ferrite magnetic powder and 90wt% of the coarse-grained ferrite magnetic powder, and then a ball milling aid (the ball milling aid is a mixture of triethanolamine, ethylene glycol, and water in a mass ratio of 0.5:0.5:10) is added into the ball mill for ball milling for 1.0 hour, and then the mixed powder is washed with water and dried, and then placed in an electric furnace for tempering at 950°C, and then pickled with a 2wt% concentration hydrochloric acid solution to make its pH value reach 6-7, and then dried and crushed to obtain a coarse and fine mixed magnetic powder, which is the bonded ferrite magnetic powder for injection molding prepared in Example 3 of the present invention.
[0123] Step C4, preparation of injection molded flexible bonded magnet: 93 parts by weight of the coarse and fine mixed magnetic powder described in step C3, 6 parts by weight of rubber adhesive, 1 part by weight of plasticizer, and 1 part by weight of stabilizer are stirred together in a mixer, and then extruded and granulated by a twin-screw extruder. The obtained pellets are injection molded on an injection machine at an injection temperature of 175-190°C and a molded sample size of Φ20×10mm, thereby obtaining an injection molded flexible bonded magnet.
[0124] Wherein, the rubber adhesive is blended by 20 parts by weight of polyvinyl chloride (PVC), 65 parts by weight of thermoplastic polyurethane elastomer (TPU) and 15 parts by weight of thermoplastic polyester elastomer (TPEE). The use of thermoplastic polyurethane elastomer (TPU) and thermoplastic polyester elastomer (TPEE) mixed as an adhesive can improve the heat resistance of the flexible adhesive magnet and enable the use temperature of the flexible adhesive magnet to reach 125°C. The polyvinyl chloride (PVC) is a SG9 model product that meets the GB / T5761-2006 standard, and its average degree of polymerization is less than 650. The use of this polyvinyl chloride can greatly improve the melt fluidity of the magnet. The plasticizer is a long-chain chlorinated paraffin environmentally friendly plasticizer, which can play a role in plasticization and lubrication. The stabilizer is an ultraviolet absorber UV531, which can improve the aging resistance of the magnet.
[0125] Specifically, the temperature gradient and other parameters of the injection molding in step C4 are shown in Table 7 below:
[0126] Table 7
[0127] One section Second paragraph Three sections Magnetizing current Cooling and holding pressure 190℃ 185℃ 175℃ 70A Operation cycle 100S
[0128] Furthermore, the prior art product 3 (the prior art product 3 uses the injection magnetic powder BMZR-3A produced by Beikuang Magnetic Material Technology Co., Ltd. and the flexible magnet BMZR-Y1 made of the injection magnetic powder BMZR-3A) is compared with the bonded ferrite magnetic powder for injection molding prepared in step C3 of Example 3 of the present invention and the injection molded flexible bonded magnet prepared in step C4 for performance and temperature aging resistance. The results are shown in the following Table 8 and Table 9:
[0129] Table 8
[0130]
[0131]
[0132] Table 9
[0133]
[0134] It can be seen from Table 8 above that the compression density of traditional ferrite magnetic powder is generally 3.3g / cm 3 The compression density of the prior art product 3 in Table 8 reaches 3.48 g / cm 3 The compression density of the bonded ferrite powder for injection molding prepared in Example 3 of the present invention reaches 3.62 g / cm 3 , and the fluidity and magnetic properties of the injection molded flexible bonded magnet prepared in Example 3 of the present invention are both better than those of the prior art product 3. It can be seen from Table 9 above that the prior art product 3 is severely deformed and cracked under the heat aging conditions of 125°C×96h, while the injection molded flexible bonded magnet prepared in Example 3 of the present invention has almost no volume change under the heat aging conditions of 125°C×96h, which means that the upper limit of the use temperature of the injection molded flexible bonded magnet prepared in Example 3 of the present invention is increased from 80°C in the prior art to 125°C, which broadens the application field of the injection molded flexible bonded magnet and increases the stability and reliability of the injection molded flexible bonded magnet.
[0135] In summary, it can be seen that the embodiments of the present invention can be used to prepare injection molded flexible bonded magnets, which can greatly improve the fluidity of bonded ferrite powder for injection molding and the magnetic properties of the injection molded flexible bonded magnets, both of which exceed the level of similar products in the prior art, and can increase the upper limit of the use temperature of the prepared injection molded flexible bonded magnets from 80°C in the prior art to 125°C, which broadens the application field of the injection molded flexible bonded magnets and increases the stability and reliability of the injection molded flexible bonded magnets.
[0136] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims. The information disclosed in the background technology section of this article is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as an admission or in any form that the information constitutes prior art known to those skilled in the art.
Claims
1. A bonded ferrite powder for injection molding, It is characterized in that The bonded ferrite magnetic powder for injection molding is prepared by adding fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns and coarse-grained ferrite magnetic powder with an average particle size of 3.0 to 6.0 microns into a ball mill for ball milling in a weight ratio of 10 to 35 wt % of the fine-grained ferrite magnetic powder, thereby obtaining a coarse-fine mixed magnetic powder; The ball milling comprises: adding a ball milling aid into a ball mill for ball milling; the ball milling aid is prepared by mixing triethanolamine, ethylene glycol and water in a mass ratio of 0.5:0.5:10; The fine-grained ferrite magnetic powder contains 0.2% to 0.4wt% of bismuth oxide, and the coarse-grained ferrite magnetic powder also contains 0.2% to 0.4wt% of bismuth oxide; 15 g of the bonded ferrite powder for injection molding was placed in a cylindrical mold with a diameter of 25 mm and pressed into a cylindrical green compact under a molding pressure of 80 KN. The thickness of the green compact was measured and the compression density was calculated. The compression density of the bonded ferrite powder for injection molding was 3.55 g / cm 3 above.
2. The bonded ferrite powder for injection molding according to claim 1, It is characterized in that The bonded ferrite powder for injection molding has a melt flow rate of 100 g or more per 10 minutes when the fluidity test is performed in the following steps 1 to 3; Step 1, 92 parts by weight of the bonded ferrite powder for injection molding, 1.0 parts by weight of a stabilizer, 1.0 parts by weight of a plasticizer and 6.0 parts by weight of a rubber adhesive are mixed in a mixer; wherein the rubber adhesive is a mixture of polyvinyl chloride, a thermoplastic polyurethane elastomer and a thermoplastic polyester elastomer in a weight ratio of 25:60:15; Step 2, kneading the mixture obtained in step 1 at 170-180° C. to form kneaded particles with an average particle size of 3-4 mm; Step 3: Place the mixed pellets obtained in step 2 on a melt flow index tester, measure the extrusion weight within 10 minutes at 190° C. and a load of 10 kg, and use it as the melt flow rate.
3. The bonded ferrite powder for injection molding according to claim 1, It is characterized in that When the bonded ferrite powder for injection molding is subjected to the intrinsic coercive force test and the residual magnetic flux density test in the following steps 1, 2, and 4, the injection molded flexible bonded magnet made by using the bonded ferrite powder for injection molding has an intrinsic coercive force of 190 kA / m or more and a residual magnetic flux density of 296 mT or more; Step 1, 92 parts by weight of the bonded ferrite powder for injection molding, 1.0 parts by weight of a stabilizer, 1.0 parts by weight of a plasticizer and 6.0 parts by weight of a rubber adhesive are mixed in a mixer; wherein the rubber adhesive is formed by mixing polyvinyl chloride, thermoplastic polyurethane elastomer and thermoplastic polyester elastomer in a weight ratio of 25:60:15; Step 2, kneading the mixture obtained in step 1 at 170-180° C. to form kneaded particles with an average particle size of 3-4 mm; Step 4: Injection mold the mixed particles obtained in step 2 into a cylindrical injection-molded flexible bonded magnet with a diameter of 20 mm and a height of 10 mm in an orientation magnetic field of 8.0 kGS at a temperature of 190°C, wherein the direction of the orientation magnetic field is parallel to the central axis of the cylinder, and use a permanent magnetometer to measure its intrinsic coercive force and residual magnetic induction intensity.
4. A method for preparing bonded ferrite powder for injection molding, It is characterized in that include: Fine-grained ferrite magnetic powder with an average particle size of 0.5 to 1.2 microns and coarse-grained ferrite magnetic powder with an average particle size of 3.0 to 6.0 microns are added into a ball mill for ball milling in a weight ratio of 10 to 35 wt % of the fine-grained ferrite magnetic powder, thereby obtaining a coarse and fine mixed magnetic powder, which is the bonded ferrite magnetic powder for injection molding according to any one of claims 1 to 3; The ball milling comprises: adding a ball milling aid into a ball mill for ball milling; the ball milling aid is prepared by mixing triethanolamine, ethylene glycol and water in a mass ratio of 0.5:0.5:10; The fine-grained ferrite magnetic powder contains 0.2% to 0.4wt% of bismuth oxide, and the coarse-grained ferrite magnetic powder also contains 0.2% to 0.4wt% of bismuth oxide; 15 g of the bonded ferrite powder for injection molding was placed in a cylindrical mold with a diameter of 25 mm and pressed into a cylindrical green compact under a molding pressure of 80 KN. The thickness of the green compact was measured and the compression density was calculated. The compression density of the bonded ferrite powder for injection molding was 3.55 g / cm 3 above.
5. An injection molded flexible bonded magnet, It is characterized in that The composition comprises the following raw materials in parts by weight: The rubber adhesive is prepared by blending 20 to 25 parts by weight of polyvinyl chloride, 60 to 70 parts by weight of thermoplastic polyurethane elastomer and 10 to 15 parts by weight of thermoplastic polyester elastomer.
6. The injection molded flexible bonded magnet according to claim 5, It is characterized in that The polyvinyl chloride is a SG9 model product that complies with the GB / T5761-2006 standard, and its average polymerization degree is less than 650; the plasticizer is an environmentally friendly long-chain chlorinated paraffin plasticizer; and the stabilizer is an ultraviolet absorber UV531.
Citation Information
Patent Citations
Ferrite powder for bonded magnets, process for the production of the powder, and bonded magnets made by using the same
CN101808943B
Ferrite powder for bonded magnet, method for producing same and bonded magnet using same
CN102388423A
Spliced magnet and ferrite magnetic powder for splicing same
CN1540687A
